Threat hunting : a guide to proactive network defense - Collins, Michael (Michael Patrick) (O'Reilly Media, 2018)
Beyond incident response and threat intelligence operations, threat hunting can provide an extra layer of defense for your company's network. In many organizations, security analysts initiate threat hunting when they spot something weird--network conditions or activity not easily explained--in an effort to catch subtle, more deeply embedded attackers. With this practical ebook, you'll explore how this method works and learn how to stage an effective threat hunting program and evaluate the results. Author Michael Collins, chief scientist for the network security and data analysis company RedJack in Washington, DC, explains why threat hunting is an ideal support for your existing security operations center. With both architecture and attacks constantly changing, proactive threat hunting will help security analysts and security managers discover how your company's assets really work. Learn about the process, goals, and benefits of threat hunting Examine your organization's readiness for threat hunting, including the resources, data, and personnel you need Delve into the process using a typical threat hunting workflow Get a brief encyclopedia of threat hunting techniques, including core concepts and situational awareness Explore resources for additional threat hunting strategies and techniques.